A market chain analysis of interisland cattle trade into South Kalimantan, Indonesia. (November 2019) - Hamdan, A; Sumantri, I; Hadi, S N; Rohaeni, E S; Yanti, N D; Chang, C
Abstract: Local cattle production in South Kalimantan (KalSel) has been unable to meet the demand, thus live cattle were imported from other islands.. Cattle imports have increased in recent years, thus local smallholders are experiencing falling prices. The objectives of this paper are to understand the market chains of cattle trading from interislands, and to assess the cost competitiveness of local cattle to the imports. Methods used in this research are market chain and gross margin analysis. Key findings are: KalSel imported approximately 5000 head live cattle per month, mainly from NTT and NTB, followed by South Sulawesi and East Java; cattle from East Java were Limousin and other crossbreeds, other provinces supplied mainly Bali cattle; interisland cattle were traded based on price per kg and actual live weight, while local cattle were based on price per head and estimation of live weight; cattle from East Java was most price competitive, followed by NTT/NTB and then South Sulawesi; in terms of taste, beef from crossbreeds was better, followed by beef from Sulawesi, and then from NTT or NTB; and finally local cattle were cost uncompetitive because of the pricing method used, small scale production and low productivity.